IMPLEMENTASI KEBIJAKAN STANDAR PELAYANAN MINIMAL BIDANG KESEHATAN DI KOTA PALU (STUDI PUSAT KESEHATAN MASYARAKAT) - Rawung, Deisi J (Katalogis, 2017)
The Research aimed was to determine and analyze the policy Implementation of theÂ  minimum service standards in Health Service in Palu City Study of Birobuli health center. The main theory in this study is Policy Implementation theory of Edward III that includes; (1) communication, (2) resources, (3) disposition, (4) Structure of Bureaucracy. The research methods using descriptive qualitative descriptive approach. The research location is in Health Centre Birobuli, informant as much as 5 people were selected purposively. Data collection was done by interviewing, observation, and documentation. Data analysis methode using the Interactive Miles and Huberman models. Based on the research result, policy implementationn of Minimum Service Standards of health in Palu (Study of Community Health Centres Birobuli), when viewed from the aspect (1) communication, (2) resources, (3) disposition, and (4) the bureaucratic structure, indicating that it is not effective, because there are still aspects that have not been adequate, namely communication, resources, disposition and bureaucratic structure which is still not running properly and optimally, it can be seen from the communication on policies SPM in Puskesmas Birobuli still have not touched understanding of the community as a user policy. Human resources still need to be improved in terms of quantity and budgetary resources are inadequate in implementing programs SPM as a whole, as well as in terms of disposition, which is still firmly in providing services according to the standard procedures and bureaucratic system of convoluted in the implementation of the program and budget financing in the Minimum Service Standards in Puskesmas Birobuli.